2005
DOI: 10.3748/wjg.v11.i30.4634
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical studies on intestinal metaplasia adjacent to gastric cardia adenocarcinoma in subjects at high-incidence area in Henan, north China

Abstract: Abstract Abstract Abstract AIM:To characterize the histochemical type and pattern of intestinal metaplasia (IM) adjacent to gastric cardia adenocarcinoma (GCA) and distal gastric cancer (GC) in Linzhou, Henan Province, China. METHODS:Alcian-blue-periodic acid Schiff and high iron diamine-Alcian blue histochemical methods were performed on 142 cases of IM, including 49 cases of GCA and 93 cases of GC. All the patients were from Linzhou, Henan Province, China, the highest incidence area for both GCA and squamous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Our results confirmed a significant difference in the proportion of IM subtypes among various EGC locations, as reported previously also in Chinese patients 29 . We showed that EGC with IM demonstrated distinct clinicopathological features, such as a significantly higher proportion of cases with non‐poorly cohesive‐carcinoma, en bloc resection, and eCura C‐1 grade.…”
Section: Discussionsupporting
confidence: 91%
“…Our results confirmed a significant difference in the proportion of IM subtypes among various EGC locations, as reported previously also in Chinese patients 29 . We showed that EGC with IM demonstrated distinct clinicopathological features, such as a significantly higher proportion of cases with non‐poorly cohesive‐carcinoma, en bloc resection, and eCura C‐1 grade.…”
Section: Discussionsupporting
confidence: 91%
“…These two chronic damages contributes to the high incidence of IM and inflammation at the cardiac mucosa (Odze, 2005;McColl, 2006). Our previous research showed that the incidence of IM in tissue adjacent to gastric cardiac adenocarcinoma is much higher than gastric cardiac biopsy tissue from normal population (Gao et al, 2005). The result suggest that IM is an important precancerous lesion.…”
Section: Discussionmentioning
confidence: 89%
“…GCA is the most common malignant tumor of digestive tract in Henan Province, China (Gao et al 2005 ). Recent decades have seen an alarming increase in the incidence of GCA, while non-cardia gastric adenocarcinoma has decreased (Abdi et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%